2021
DOI: 10.1093/gerona/glab138
|View full text |Cite
|
Sign up to set email alerts
|

The Indigenous South American Tsimane Exhibit Relatively Modest Decrease in Brain Volume With Age Despite High Systemic Inflammation

Abstract: Brain atrophy is correlated with risk of cognitive impairment, functional decline, and dementia. Despite a high infectious disease burden, Tsimane forager-horticulturists of Bolivia have the lowest prevalence of coronary atherosclerosis of any studied population and present few cardiovascular disease (CVD) risk factors despite a high burden of infections and therefore inflammation. This study (A) examines the statistical association between brain volume and age for Tsimane, and (B) compares this association to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…The prevalence of chronic disease burden is also highest in South India (Dandona et al, 2017; Singh et al, 2019), which may contribute to a low HAS. Since tribes often report better health in later life due to their lifestyle (Irimia et al, 2021; Irshad et al, 2022), the high proportion of tribal populations in the North-east states (Mohindra & Labonté, 2010) may be the reason for the region’s higher mean HAS. Differences in sociocultural factors could be another reason for the difference in healthy ageing, such as family size and attitude towards caring for the elderly (Ahmed, 2020; Samanta et al, 2015), which are different across regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of chronic disease burden is also highest in South India (Dandona et al, 2017; Singh et al, 2019), which may contribute to a low HAS. Since tribes often report better health in later life due to their lifestyle (Irimia et al, 2021; Irshad et al, 2022), the high proportion of tribal populations in the North-east states (Mohindra & Labonté, 2010) may be the reason for the region’s higher mean HAS. Differences in sociocultural factors could be another reason for the difference in healthy ageing, such as family size and attitude towards caring for the elderly (Ahmed, 2020; Samanta et al, 2015), which are different across regions.…”
Section: Resultsmentioning
confidence: 99%
“…This surprising result is consistent with Irshad et al (2022). A study in Latin America showed that compared to Europeans and Americans, the Tsimane tribe of Bolivia had better health at a later age, especially in terms of cognitive ability (Irimia et al, 2021). Tribes’ reliance on physical labour for survival, such as farming, hunting and fishing, may explain why they have relatively better health as they age.…”
Section: Resultsmentioning
confidence: 99%
“…The Yanomami, a people living in the Venezuelan–Brazilian Amazon, are among the healthiest in terms of their blood lipid profiles, with no sign of obesity, at least until they leave their communities and enter what can loosely be termed the “modern world” [ 22 ], suggesting that “westernisation affects human microbiome diversity” [ 23 ]. Likewise, the Tsimane, from the Bolivian Amazon, not only show low levels of cardiovascular disease [ 24 ], but also little dementia, despite their high systemic inflammation [ 25 ]. Lest people think that this is unique to South America, the Hadza, a people from Tanzania, were similarly healthy and, moreover, were found not to carry any strains of Bifidobacteria [ 26 ], a group of microorganisms currently held to confer health benefits [ 27 ], albeit not very successfully [ 28 ].…”
Section: Health Versus Pollution: the Degraded Microbiomementioning
confidence: 99%
“…Fortunately, there are people who live in relatively unpolluted parts of the world who are already cooperating with medical investigators. Such people, including the Tsimane [ 25 ] and the Hadza [ 26 ], may be able to help in the search for relevant microeukaryotes. Principles have been established for the compensation of people for the use of their knowledge in medical advances, and such principles could be applied here [ 144 ].…”
Section: Microbiome-function Deficiency Disease: Cure Control or Prev...mentioning
confidence: 99%
“…In this respect, there are still people living on the fringes of modern civilisation who have not yet suffered the worst effects of such poisoning and, by and large, do not exhibit the symptoms of non-communicable disease. The Tsimane, for example, largely healthy in spite of having a high systemic inflammation, are already engaging with medical teams [113] and may be willing to support further efforts to fully understand the microbiome. Note that adequate compensation could be provided for such assistance using, for example, the "principle of reciprocity" as has been developed for cancer medicines [114].…”
Section: Microbiome Function Deficiency Disease: Cure Control or Prev...mentioning
confidence: 99%